Survival prediction in peritoneal mesothelioma: a nomogram based on SEER data and a Chinese cohort - Fang, Yuting; Xiang, Midan; Jiang, Zhichao; Li, Hongrui; Yuan, Guangwen; Pei, Wei; Li, Wenbin; Sun, Yongkun (Frontiers in Endocrinology, 2024)
Objective: This study aimed to develop a nomogram predicting overall survival (OS) of patients with peritoneal mesothelioma (PeM) using data from the Surveillance, Epidemiology, and End Results (SEER) database and a Chinese institution. Methods: A total of 1,177 PeM patients from the SEER database were randomized into training and internal validation cohorts at a 7:3 ratio. An external validation cohort consisting of 109 patients was enrolled from a Chinese institution. The nomogram was constructed based on variables identified through multivariate Cox regression analysis and evaluated by consistency indices (C-index), calibration plots, and receiver operating characteristic (ROC) curves. Patients were stratified into different risk categories, and Kaplan-Meier survival analysis was used to assess OS differences among these groups. Results: The nomogram, incorporating age, gender, histological type, T stage, M stage, and surgical status, demonstrated strong predictive capability with C-index values of 0.669 for the training cohort, 0.668 for the internal validation cohort, and 0.646 for the external validation cohort. The nomogram effectively stratified patients into high-risk and low-risk groups, with the high-risk group exhibiting significantly poorer OS (P < 0.05). Multivariate analysis confirmed gender, age, surgical intervention, and M stage as independent prognostic factors (P < 0.05). Specifically, male gender, older age, and unspecified M stage were linked to worse outcomes, while surgical intervention was associated with improved survival. Conclusion: The nomogram provides a reliable tool for predicting the survival in PeM patients, facilitating more informed treatment decisions. Key independent prognostic factors include gender, age, surgical intervention, and M stage.